The stock market's reaction to the mandatory disclosure of ESG information - Mateus Del Col Lopes; Michele Nascimento Jucá (Revista Ambiente Contábil, 2025)
Purpose: Analyze the impact of mandatory disclosure of ESG information in Brazil on the price of shares in the local market.